2020
DOI: 10.1126/sciadv.abb5769
|View full text |Cite
|
Sign up to set email alerts
|

3D touchless multiorder reflection structural color sensing display

Abstract: The development of a lightweight, low-power, user-interactive three-dimensional (3D) touchless display in which a human stimulus can be detected and simultaneously visualized in noncontact mode is of great interest. Here, we present a user-interactive 3D touchless sensing display based on multiorder reflection structural colors (SCs) of a thin, solid-state block copolymer (BCP) photonic crystal (PC). Full-visible-range SCs are developed in a BCP PC consisting of alternating lamellae, one of which contains a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 35 publications
2
52
0
Order By: Relevance
“…Effective Young’s modulus of top layer ( E eff ) after swelling-deswelling cycles from rule of mixture was obtained of approximately 3 GPa by the relation of E eff = V PS E PS + V P2VP E P2VP . The estimated E QP2VP-gel was approximately 40 MPa, which is in good agreement with the value of a typical elastomer ( 23 ). We also calculated the maximum height of a swollen screw dislocation upon EtOH swelling based on the scheme in fig.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Effective Young’s modulus of top layer ( E eff ) after swelling-deswelling cycles from rule of mixture was obtained of approximately 3 GPa by the relation of E eff = V PS E PS + V P2VP E P2VP . The estimated E QP2VP-gel was approximately 40 MPa, which is in good agreement with the value of a typical elastomer ( 23 ). We also calculated the maximum height of a swollen screw dislocation upon EtOH swelling based on the scheme in fig.…”
Section: Resultssupporting
confidence: 82%
“…The TEM projection of the 20-nm-thick section sample strongly resembles that of a nonsingular spiral structure like that of a biphasic helicoid, which serves as a continuous pathway for the diffusion of the swelling agent from the top to the bottom of the film ( Fig. 2A ) ( 5 , 6 , 23 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, reflected light of each interface in the stack interferes coherently under conditions satisfying Bragg’s law for the stack: mλ = 2( n h d h + n l d l )sinθ, where n h , d h , n l , and d l are the refractive indices and thicknesses of the high- and low-index layers, respectively. Reports of such Bragg stacks composed of organic/inorganic hybrid materials [ 93 , 94 ], inorganic materials [ 95 , 96 , 97 ], and organic materials [ 98 ] have demonstrated controllable and bright structural colors. Kou et al [ 93 ] recently reported the performance of a colorimetric Bragg stack humidity sensor responding to human breath, shown in Figure 11 .…”
Section: Types Of Fast-response Humidity Sensormentioning
confidence: 99%